Above-ground bole biomass and carbon stock of recreational trees at Agodi Gardens, Oyo State, Nigeria - Oluwagbemiga, Ige Peter; Olalekan, Hussein Ismaheel (Journal of Forests, 2024)
This study used allometric equations to evaluate the biomass and carbon stock of recreational trees at Agodi Gardens in Ibadan Metropolis. Stratified sampling technique was used to delineate 15 plots (25m x 25m). Six allometric equations were selected to estimate Aboveground Biomass (AB) of the tree species. Models selected were assessed based on highest adjusted coefficient of determination (AdjR2), significant F-ratio (P<0.05) and least Root Means Square Error (RSME). A total of 220 trees belonging to 18 species were encountered. The dominant Diameter at Breast Height (DBH) and Height (Ht) were 62.8cm and 39.1m, respectively for Alstonia bonnei and Elaeis guineensis. The mean AB/ha was 2.8006Kgha-1 and the highest carbon stock of 3.332147 x 10-4 was recorded for Khaya ivorensis. Equation C= 2.6 x 10-7+ln (AB) + lnDBH²+lnHt (AdjR²=99%), gave the best fit to estimate carbon stock in the study area. The study found a significant relationship between AB, DBH and Ht, with a high correlation between DBH and Ht (P-value=0.00). Hence, as the DBH increases, the Ht increases with an increase in AB. Most trees had low slenderness coefficients (<70). The developed allometric model improved the prediction of aboveground stem biomass and carbon stock, making it useful for future research.